Skewed pretransplant lymphocytes subpopulations correlate with opportunistic infection onset within the first two years following kidney transplantation - Beldi-Ferchiou, Asma; Runyo, Florence; Canoui-Poitrine, Florence; Peiffer, Bastien; Dediu, Benyamin Mattei; Champy, Cécile Maud; Oniusciuk, Julie; Melica, Giovanna; Usureau, Cédric; Joher, Nizar; Cohen, José; Grimbert, Philippe; et al. (Frontiers in Immunology, 2025)
IntroductionAfter kidney transplantation (KT), there is no reliable assessment of the immunosuppressive state. We analysed pre-KT T-, B- and NK-cell populations in relation to the occurrence of opportunistic infections (OI) or acute rejection (AR) after KT.MethodsWe included 422 adult KT recipients from 01/2016 to 09/2020. Immune cells were analysed using flow cytometry in 283 recipients before KT in three groups: AR, OI or no event within 24 months after KT.ResultsThere were 49 recipients in the OI group, 44 in the AR group and 190 in the control group. Before KT, higher absolute counts and percentages of NK cells (p=0.001 and p=0.007 respectively), elevated absolute counts of plasmablasts and CD21-CD38- B cells (age-associated B cells) (p=0.045 and p=0.028 respectively), and a lower proportion of CD3+ T cells (p=0.022) were independently associated with the occurrence of OI within two years following kidney transplantation (KT). In recipients with OI occurring before three months, only absolute count of NK cells before KT remained independently associated with the occurrence of OI (p=0.002). None of the studied immune cell population was associated with AR.ConclusionOur results suggest that higher levels of pretransplant NK cells and age-associated B cells are correlated with the occurrence of OI within two years after KT. This result may improve stratification of individualized infectious risk prior to KT.